Curious George. A very monkey Christmas - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Public Broadcasting Service (U.S.); Universal Studios Home Entertainment (Firm) (Universal City, Calif. : Universal Studios Home Entertainment, 2009)
"George and the Man with the Yellow Hat are having a very merry time counting down the days until Christmas. There's only one puzzle: neither of them can figure out what to give the other for a present ... Will they be able to find the answers before Christmas morning?"--Publisher.
Widescreen.
Based on characters created by Margret and H.A. Rey, and the PBS television program, Curious George.
DVD; Dolby Digital, surround stereo.
Dialogue in English with English subtitles for the hearing impaired (SDH) or Spanish or French subtitles.
Keywords: Curious George (Fictitious character) -- Juvenile films; Christmas -- Juvenile films; Children's television programs; Animated television programs; Television programs for the hearing impaired